Antibody Response Post-COVID-19 Vaccination in Patients With Chronic Myeloid Leukemia With Comparison Between Comirnaty and CoronaVac Vaccine - Kuan, Jew Win; Tan, Cheng Siang; Anselm, Su Ting; Vaenessa, Noni; Whilemena Upam, Herman Ulok Melina; Ummi Syafiqah, Abdorahman; Joseph Niler, Bimbang; Lela, Suut; Asri, Said (SAGE Publications Inc., 2022)
Dear Editor Chronic myeloid leukemia (CML) is a type of myeloproliferative neoplasm characterized by an oncogenic fusion gene, BCR-ABL1. Most CML patients present at chronic phase, ~90%,1 when BCR-ABL1 tyrosine kinase inhibitor (TKI) is the recommended first-line treatment. Antibody response after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination in CML patients is concerned due to probable CML-induced and/or TKI-induced immunosuppression. To our knowledge, two studies reported antibody response post-SARS-CoV-2 vaccine in CML patients.2,3 A study reported anti-spike SARS-CoV-2 IgG (IgG-S) responses > 14 days after a dose of Comirnaty (Comirnaty or BNT162b2, Pfizer-BioNTech) (n = 1) or ChAdOx1 (ChAdOx1 nCoV-19 or AZD1222, AstraZeneca-Oxford) (n = 11) vaccine.2 Seroconversion rate post-ChAdOx1 was lower than control group, 8/11 (73%) versus 58/63 (92%).2 A study reported response 3 weeks after a dose of Comirnaty (n = 16) using a different laboratory methodology.3